Introductory computer methods and numerical analysis - Pennington, Ralph H. (New York : Macmillan, 1970)
An update of the first edition on the numerical analysis method of dealing with researches in the computer areas.
Includes index
kjo 15/01/2019
Loans
Keywords: Numerical analysis---Data processing; FORTRAN (Computer program language)